Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

candeebabee

  • 3 years ago

lve for x: 3(x + 1) = −2(x − 1) − 4

  • This Question is Closed
  1. Fall12-13
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    1. Open brackets. 2. Take all terms containing x to one side. 3. Solve. 3x + 3 = -2x + 2 - 4 3x + 2x = 2 - 4 - 3 5x = 2 - 7 5x = -5 x = -5/5 = -1

  2. candeebabee
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    ahh thank you so much!(:

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy